Case and number in English and in Pangasinan a contrastive analysis - Magat, Belen (Parayno)
The study seeks to determine the similarities and differences in the structures of two languages, Pangasinan and English, in terms of case and number. It specifically describes and compares the two systems based on these three levels: morphology, syntax, and semantics to find out the difficulties that a Pangasinan learner will meet in learning English as a second language.